Perekrutan dan Kegiatan Anak Sebagai Kurir dalam Jaringan Peredaran Narkoba - Anton Prasetyo* (Airlangga Development Journal, 2019)
Polrestabes satresnarkoba data for the third quarter in surabaya until 2018 in total there are 20 suspects with the drug as a courier. As many as 15 people have as users, dealers and courier 2 3 .So based on the advanced analysis was needed on how the recruitment of children as a courier in the trafficking of drugs   and   analyzes   on efforts  to  satresnarkoba  polrestabes  surabaya  in reducing activity the recruitment of  children  as  drug  couriers  .The  statute used  is  research  approach  ,  the conceptual approach and empirical legal using interviews as a primary data and the cases handled satresnarkoba polrestabes surabaya as secondary data. The pattern of recruitment carried out to make children as drug couriers is  through the use of weak  economic conditions of children and the inability of children to work so that children have no other way to get money for drugs other than being couriers. The use of child loyalty to his group colleagues, the use of trap patterns and threats is another way of recruiting children in drug syndicates. The effort to handle the recruitment of children as drug couriers by the Satresnarkoba Polrestabes Surabaya  is  done  in a   pre-emptive   manner,   namely   through   integrated coordination   with   BNN Surabaya   City   by   exchanging   information   about children caught in drugs and drug syndicates detected. The formation of anti- drug   student  cadres  and  drug counseling for parents of students is a pre- emptive  method  carried  out  by  the Satresnarkoba  Polrestabes  Surabaya. While  the  repressive  method  is  carried  out by the application of criminal procedural  law,  especially  for  drug  dealers  and dealers  to  break  drug networks. Firm and measurable actions and various drug raids operations are expected to break the chain of drug trafficking, especially those targeting children to be used as couriers.